2004
DOI: 10.1086/420821
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Pneumococcal Pneumonia Caused by Antibiotic-Resistant Strains in Asian Countries: A Study by the Asian Network for Surveillance of Resistant Pathogens

Abstract: To evaluate the clinical outcomes of pneumococcal pneumonia caused by antibiotic-resistant strains in Asian countries, we performed a prospective observational study of 233 cases of adult pneumococcal pneumonia in 9 Asian countries from January 2000 to June 2001. Among 233 isolates, 128 (55%) were not susceptible to penicillin (25.3% were intermediately susceptible, and 29.6% were resistant). Clinical severity of pneumococcal pneumonia was not significantly different between antibiotic-resistant and antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
4
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 27 publications
7
42
4
5
Order By: Relevance
“…In our study, 11 double ermB-and mefA-positive isolates also had low-level telithromycin susceptibility (MIC ϭ 0.06 to 1 mg/liter; MIC 90 ϭ 0.5 mg/liter) and greater resistance than solely ermB-positive isolates or solely mefA- Reported risk factors for macrolide-resistant S. pneumoniae, such as the previous use of antibiotics and hospital admission, were not confirmed in our study. Although Song et al reported that older age and, as a result, higher PSI scores, were independent predictors of erythromycin-resistant pneumococcal pneumonia (30), age and PSI score were not associated with the presence of macrolide resistance genes in our study. This was probably because of the high prevalence of erythromycin-resistant S. pneumoniae among CAP patients with each genotype.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In our study, 11 double ermB-and mefA-positive isolates also had low-level telithromycin susceptibility (MIC ϭ 0.06 to 1 mg/liter; MIC 90 ϭ 0.5 mg/liter) and greater resistance than solely ermB-positive isolates or solely mefA- Reported risk factors for macrolide-resistant S. pneumoniae, such as the previous use of antibiotics and hospital admission, were not confirmed in our study. Although Song et al reported that older age and, as a result, higher PSI scores, were independent predictors of erythromycin-resistant pneumococcal pneumonia (30), age and PSI score were not associated with the presence of macrolide resistance genes in our study. This was probably because of the high prevalence of erythromycin-resistant S. pneumoniae among CAP patients with each genotype.…”
Section: Discussioncontrasting
confidence: 95%
“…Recent studies have defined risk factors for macrolide resistance in pneumococcal pneumonia and invasive infections. These included previous hospital admission, penicillin resistance, advanced age, a higher pneumonia severity index (PSI) score, human immunodeficiency virus infection, and previous penicillin or macrolide use (1,30,35). Risk factors for antimicrobial resistance are useful for avoiding inappropriate therapy.…”
mentioning
confidence: 99%
“…[14][15][16][17][18] The main reasons for abandoning penicillin in the treatment of pneumococcal pneumonia are the progressive increase of penicillin resistance in S. pneumoniae and the absence of a consensus on optimal dosage. 23 Pharmacokinetics and pharmacodynamics data suggest that, in the treatment of pneumonia, beta-lactam antibiotics are effective against pneumococci with MICs of up to 4 µg/mL.…”
Section: Agentmentioning
confidence: 99%
“…[12][13][14] Later multicenter studies confirmed these results. 15,16 On the basis of these findings and of a review and S. pneumoniae strains were isolated from blood cultures using the BacT/ALERT ® detection system (Biomérieux, France), whereas pleural fluid specimens were cultured on chocolate agar and sheep blood agar (Biomérieux, Rio de Janeiro, Brazil). Pure cultures were taken from blood agar.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of SP-positive patients with CAP have demonstrated similar findings, even with sicker patients and variable antibiotic administration. 18 Moreover, because most patients recover, it is arguable that the initial therapeutic decision is less important than ensuring reliable follow-up to identify the small percentage of patients who do not fair well. Finally, from our analyses, no factors are readily apparent to assist clinicians in estimating who might experience a relapse after discharge, at least in those patients with class I-III CAP.…”
Section: Discussionmentioning
confidence: 99%